(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Extracerebral tumors of the posterior cranial fossa, due to the formation of complex topographic and anatomical relationships with the brainstem, often lead to a disruption of its function, but the degree of brainstem damage is most often determined only on the basis of clinical data. Signs of brainstem damage in tumors of this localization are observed in 65-80%, among them, irritation symptoms predominate, which make up 65%, conduction disorders are noted in 38%, damage to the cranial nerves on the side of the tumor is observed in 28%.